2011
DOI: 10.1002/chem.201101265
|View full text |Cite
|
Sign up to set email alerts
|

Small Pd Nanoparticles Supported in Large Pores of Mesocellular Foam: An Excellent Catalyst for Racemization of Amines

Abstract: Highly dispersed palladium nanoparticles (1-2 nm) supported in large-pore mesocellular foam (MCF; 29 nm) were synthesized. The Pd-nanocatalyst/MCF system was characterized by transmission electron microscopy (TEM), powder X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The performance of the Pd nanocatalyst obtained was examined for amine racemization. The Pd nanocatalyst showed higher activity and selectivity toward racemization of (S)-1-phenylethyl amine than any other amine racemization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 38 publications
2
61
0
Order By: Relevance
“…In the presence of benzoquinone the Pd(0) species formed in situ is efficiently reoxidized to active Pd(II), and the recovered heterogeneous catalyst maintains its high catalytic and can be reused four times without detectable deactivation. In a control experiments, we found that in the presence of benzoquinone also the Pd(0)-AmP-MCF 30,31 was activated and shown to catalyze the lactonization of 4-pentynoic acid in good yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of benzoquinone the Pd(0) species formed in situ is efficiently reoxidized to active Pd(II), and the recovered heterogeneous catalyst maintains its high catalytic and can be reused four times without detectable deactivation. In a control experiments, we found that in the presence of benzoquinone also the Pd(0)-AmP-MCF 30,31 was activated and shown to catalyze the lactonization of 4-pentynoic acid in good yield.…”
Section: Introductionmentioning
confidence: 99%
“…24,25,29 We have recently reported on the preparation of a heterogeneous catalyst based on Pd nanoparticles immobilized on amino-functionalized siliceous mesocellular foam (Pd(0)-AmP-MCF). 30,31 Mesocellular foam (MCF) is a mesoporous material that has proven to be an excellent support for both chemical as well as biological catalysts, mainly due to its high surface area, high pore volume and adjustable pore size. [32][33][34] Several organic transformations have successfully been accomplished with our novel Pd(0)-catalyst, such as aerobic oxidation of primary and secondary alcohols, 31 transfer effect of the change in the different reaction parameter, the reaction time for the screen was chosen to 1 h. The optimization of the reaction conditions commenced with a screening of a series of bases.…”
Section: Introductionmentioning
confidence: 99%
“…Among the reactions explored, we had developed an allylic alcohol oxidation/Michael/ carbocyclization catalytic relay using a bench-stable palladium complex (Pd(PPh 3 ) 4 ) and a simple chiral amine with molecular oxygen as the terminal oxidant [48]. Palladium is a powerful and versatile transition metal, which can be immobilized on various solid supports and next be used as a heterogeneous catalyst for efficient chemical reactions [49][50][51][52][53][54][55][56]. In this context, we recently disclosed that enantioselective carbocyclizations could be performed by the synergistic action of a heterogeneous palladium catalyst and a chiral amine co-catalyst [57].…”
Section: Resultsmentioning
confidence: 99%
“…Other siliceous materials, such as mesocellular foams, ordered mesoporous materials, and mesoporous spheres, have been similarly used for nanoparticle stabilization. 78,79 Choudhary et al, for instance, has used layered double hydroxides for encapsulating Pd-NPs that are active for Stille C C coupling reactions. 80 Merrifield resins, usually used for automated peptide synthesis, have also been used as metal nanoparticle supports, albeit with added functionalities.…”
Section: Protection Of Catalytic Nanoparticles Against Agglomerationmentioning
confidence: 99%